Respuesta detoxificante en larvas Apis mellifera expuestas a intensificación agrícola - Macri, Ivana Noelia; Nery, Denise; Latorre Estivalis, Jose M.; Cristos, Diego Sebastian; Zavala, Jorge Alberto; Farina, Walter Marcelo (Asociación Argentina de Ecología, 2025)
Poster